Pengembangan Media Flashcard Berbasis Augmented Reality Keragaman Jamur Makroskopis Divisi Ascomycota di Tahura Sultan Adam Mandiangin sebagai Penunjang Pembelajaran Biologi di SMA - Rini Salma Nabila; Riya Irianti; Nurul Hidayati Utami (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Current technological advancements require the use of engaging, interactive, and context-based educational media to enhance students’ motivation and understanding. This study aims to develop augmented reality-based flashcard media on the diversity of macroscopic fungi in the Ascomycota division and to test the suitability, feasibility, readability, and student responses to the media. The development of augmented reality-based flashcard media refers to Thiagarajan’s 4D model, limited to the disseminate stage. Three experts served as subjects for the suitability and feasibility tests, and 15 students who had studied biodiversity material participated in the readability and response tests, using an assessment instrument in the form of a questionnaire with a rating scale of 1 to 5. Based on the research results, the developed media received an average suitability score of 4.42 (very suitable), a feasibility of 4.52 (very feasible), a readability of 4.30 (very good), and students response of 4.35 (very good). Therefore, these augmented reality-based flashcards are deemed suitable as a supporting tool in biology education, particularly for the concept of biodiversity within the fungi subtopic.